Vertigo [videorecording (DVD)] - Hitchcock, Alfred, 1899-1980; Hitchcock, Alfred, 1899-1980; Stewart, James, 1908-1997; Novak, Kim; Bel Geddes, Barbara; Helmore, Tom; Boileau-Narcejac (Alfred Hitchcock collection., 2012)
San Francisco police detective Scottie Ferguson is forced to retire when a freak accident gives him a severe fear of heights. When a rich shipbuilder hires Scottie to follow his wife, who may be suicidal, Scottie finds himself falling in love with her. Eventually Ferguson becomes obsessed with the chance to re-create her in another woman.